2017
DOI: 10.5507/fot.2016.025
|View full text |Cite
|
Sign up to set email alerts
|

A revision of the genus Geitlerinema and a description of the genus Anagnostidinema gen. nov. (Oscillatoriophycidae, Cyanobacteria)

Abstract: Abstract:The simple filamentous cyanobacterial genus Geitlerinema is heterogeneous. At least two distinct phylogenetic clades can be derived from the set of most common freshwater Geitlerinema species. Our revision is based on the original description of the type species G. splendidum aka Oscillatoria spendida and on molecular sequencing of morphologically relevant strains. The revised Geitlerinema contains only one species according to morphological similarity with its original description. Consequently, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 22 publications
3
38
0
3
Order By: Relevance
“…PCC7105, recognized as the reference strain for the marine species of this genus according to Bergey's Manual 1 . This clade was phylogenetically distant from other freshwater Geitlerinema clades which are consistent with previous reports 19,32 . Recently, Strunecký and coworkers revised the genus of Geitlerinema that Geitlerinema splendidum was only one species according to the morphological similarity with its origin description but other Geitlerinema or Leptolyngbya species was proposed to transfer into Anagnostidinema gen. nov. 32 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…PCC7105, recognized as the reference strain for the marine species of this genus according to Bergey's Manual 1 . This clade was phylogenetically distant from other freshwater Geitlerinema clades which are consistent with previous reports 19,32 . Recently, Strunecký and coworkers revised the genus of Geitlerinema that Geitlerinema splendidum was only one species according to the morphological similarity with its origin description but other Geitlerinema or Leptolyngbya species was proposed to transfer into Anagnostidinema gen. nov. 32 .…”
Section: Discussionsupporting
confidence: 92%
“…This clade was phylogenetically distant from other freshwater Geitlerinema clades which are consistent with previous reports 19,32 . Recently, Strunecký and coworkers revised the genus of Geitlerinema that Geitlerinema splendidum was only one species according to the morphological similarity with its origin description but other Geitlerinema or Leptolyngbya species was proposed to transfer into Anagnostidinema gen. nov. 32 . Our result and the previous study clearly demonstrated that marine Geitlerinema is phylogenetically distant from other freshwater Geitlerinema and might be separated into other genera of cyanobacteria.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Unfortunately, this circumscription is so broad that numerous genetically distinct strains and species were assigned to Leptolyngbya based on morphology, even though recent phylogenetic studies have demonstrated that the genus is polyphyletic and in need of taxonomic revision , Osorio-Santos et al 2014. This revisionary work has commenced, and over a dozen novel genera have been split out of Leptolyngbya thus far (Abed et al 2002, Turicchia et al 2009, Perkerson et al 2011, Taton et al 2011, Zammit et al 2012, Dadheech et al 2012, Vaz et al 2015, Song et al 2015a, 2015b, Miscoe et al, 2016, Sciuto et Moro 2016, Sciuto et al 2017, Strunecký et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Cells are 2-4 times longer than wide. The salient diacritic feature is the morphology of trichomes without sheaths [19]. The morphological description G. splendidum has not yet been clearly published, although the images and phylogeny were documented in Hasler et al [20].…”
Section: Alga Descriptionmentioning
confidence: 99%